The interplay of genetic variation and regulation of long noncoding RNAs in colorectal cancer - Abdel-Motaleb, Amany (AUC Knowledge Fountain, 2018)
Background: Colorectal cancer (CRC) is the third leading cause of death worldwide comprising ~8% of cancer deaths per year. The survival rates of metastatic CRC is 13% because of the lack of successful treatment due to a lack of understanding of the scope and environment of stage IV CRC. Materials and Methods: The transcripts of five normal colon mucosa tissue samples and their matched five stage IV CRC samples were chosen and analyzed from the dataset with the GEO Accession GSE50760. The Tuxedo Suite pipeline was used to determine the differentially expressed genes (DEGs) with a fold change cut off of 0.5 and -0.5 and a p value cut off of 0.05. Using the the DEG list, PANTHER database was used for pathway enrichment. LncRNA2Target database was used to find associated long non coding RNAs (lncRNAs) of the genes of interest. The Integrated Genome Viewer (IGV) was used to visualize any mutations or variations among the genes of interest. DeepSEA was used to functionally predict any potential novel SNPs. Using literature along with the results from PANTHER, lncRNA2Target, and IGV a novel connection was deduced. Results: There were 5,303 DEGs. The Wnt pathway had the greatest portion of DEGs indicating pathway activity. Interestingly, a number of inhibitors of the Wnt pathway were also upregulated including WIF1 and SFRP4. LncRNA2Target analysis showed that HOTAIR, a lncRNA, has a number of target genes and effectively silenced all of its targets except for WIF1 and CD82 in this dataset. WIF1, CD82, and SFRP4 has increased fold change values of 5.165, 1.05, 2.121, respectively. Additionally, lncRNAs, UCA1 and CRNDE, were found to positively regulate WNT5A, WNT2 and WNT3 and were upregulated. Using the integrative genome viewer, 10 SNPs were found in WIF1, SFRP4, CD82, WNT5A, and UCA1 of which one was novel. The potentially novel SNP in CD82 was functionally predicted to create a binding site with ZBTB7A. Additionally, CDKN2A and CDKN2B were found to have decreased expression with a fold change value of -2.266. Discussion: One synonymous SNP was in WIF1 and CD82. The missense SNPs in SFRP4 and CD82 are likely causing protein dysfunction resulting in ill-inhibition of the WNT pathway and metastasis, respectively. The novel SNP was found in CD82 at the location chr11:44,619,242 in the 3’ untranslated region. Functional prediction showed that this SNP may create a binding site with ZBTB7A which may be repressing CD82 function. Although most of the SNPs found were recorded to result in synonymous codons, the prevalence and frequency of these SNPs in these vital genes requires further investigation to confirm whether if these SNPs are coincidental or if they are damaging. Moreover, it is also probable that WIF1 and SFRP4 may be competing with UCA1 to exert their effects on WNT5A. CRNDE may also be competing to ultimately positively regulate WNT2 and WNT3. Together with the SNPs, HOTAIR may not be able to silence WIF1 and CD82, WIF1 and SFRP4 are ineffective in inhibiting the WNT ligands, the missense and the potentially novel SNPs in CD82 may be the cause for the lack of metastasis suppression. Finally, the downreglulation of CDKN2A and CDKN2B may be due to environmental and/or ethnic causes as shown in previous studies with Egyptian and Chinese CRC patients.